Anaphylactic release of mucosal mast cell protease and its relationship to gut permeability in Nippostrongylus-primed rats. - King, S J (1984)
The systemic secretion of rat mucosal mast cell protease (RMCPII) was examined in Nippostrongylus-primed rats injected intravenously with N. brasiliensis whole worm antigen. The secretory response in primed rats was both time- and dose-dependent whereas no RMCPII was present in the sera of naive rats challenged with antigen. RMCPII was detected in the sol and gel phases of intestinal perfusates, the release of enzyme into the gut lumen occurring very rapidly after challenge in immune rats. Mucosal permeability, assessed by measuring the passage of Evan's blue from the blood into the gut lumen was both time- and dose-dependent and reflected the combined capillary and epithelial permeability. Although the release of RMCPII into the gut lumen occurred more rapidly than the intraluminal accumulation of Evan's blue, these two events were highly correlated. There were, in addition significant correlations between the systemic and enteric secretion of RMCPII and the enteric accumulation of Evan's blue. These results indicate that RMCPII may have a role in altering intestinal mucosal permeability during systemic anaphylaxis in the rat.